YIA5 PKCδ deficiency accelerates neointimal lesions in a mouse model of vascular injury involving delayed re-endothelialisation and vasohibin-1 accumulation. Issue 17 (26th August 2010) - Bai, Xue; Margariti, Andriana; Zeng, Lingfang; Hu, Yanhua; Xu, Qingbo
Abstract : Objective: Protein kinase C (PKC) δ functions as a signal transducer mediating several essential functions of cell proliferation and apoptosis. However, the effect of PKCδ on neointimal formation is currently unknown. In this study, we used a vascular injury model in PKCδ knockout mice to investigate the role of PKCδ in the lesion development and underlying mechanism. Methods and results: 3 weeks after wire injury of femoral arteries, neointimal lesions were significantly increased in PKCδ−/− mice compared with wild-type animals. Immunohistochemical staining revealed that total numbers of smooth muscle cells and macrophages in the lesions were markedly elevated without the alterations of the ratio between these two types of cells. To further study the mechanisms of PKCδ-mediated increase in the lesion, an in vivo endothelial migration model was established to evaluate endothelial wound healing after wire injury. Data indicate that re-endothelialisation of the injured vessel was markedly delayed in PKCδ−/− mice that coincided with more severe intimal hyperplasia. When endothelial cells were cultivated from cardiac tissues of PKCδ−/− and PKCδ+/+ mice, the ability of cell migration was significantly reduced in PKCδ−/− mice, but no difference in proliferation and apoptosis was found. This altered endothelial migration was also verified by PKCδ inhibitor and siRNA techniques in wild-type cells. Interestingly, vasohibin-1, an anti-migration protein, was elevated in endothelial cells derived from PKCδ-deficient mice, which was identified largely owing to delayed protein degradation mediated by PKCδ. Downregulation of vasohibin-1 restored the migration rate of PKCδ−/− endothelial cells to a level similar to that in wild-type cells. Conclusion: Our data provide the first evidence that PKCδ-enhanced neointima formation occurs mainly due to delayed re-endothelialisation, which is mediated by increased cellular vasohibin-1 that is regulated by PKCδ.